PENGARUH COUNTRY OF ORIGIN TERHADAP LOYALITAS PELANGGAN DENGAN BRAND IMAGE SEBAGAI VARIABEL INTERVENING (SURVEI KONSUMEN PRODUK SMARTPHONE SAMSUNG DI PEKANBARU) - Miranda, Boby Prasetio; Karneli, Okta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to determine the effect of country of origin on customer loyalty with brand image as an intervering variable for consumer surveys of Samsung smartphone products in Pekanbaru. The independent variable is country of origin (X) and the intervening variable is brand image (Z). Meanwhile, what is used as the dependent variable (Y) is customer loyalty. This research uses a questionnaire with a scale of measurement using a Likert scale. The analysis technique used is SEM and PLS analysis. Data analysis using linear regression analysis using SmartPLS 3.3 softwareThe population in this study were 100 consumers of Samsung smartphone products in Pekanbaru who were obtained using the Slovin formula. The results of the tests conducted show that country of origin has a positive and significant effect on customer loyalty, country of origin has a positive and significant effect on customer loyalty, brand image has a positive and significant effect on customer loyalty and country of origin has a positive and significant effect on customer loyalty with brand image as a intervening variables.Keywords: Country of Origin, Brand Image, Customer Loyalty.